2018
DOI: 10.1159/000487180
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-223 Targeting STIM1 Inhibits the Biological Behavior of Breast Cancer

Abstract: Background/Aims: To investigate the cellular effects and clinical significance of microRNA-223 (miR-223) in breast cancer by targeting stromal interaction molecule1 (STIM1). Methods: Breast cancer cell lines (T47D, MCF-7, SKB-R3, MDA-MB-231 and MDA-MB-435) and a normal breast epithelial cell line (MCF-10A) were prepared for this study. MiR-223 mimics, anti-miR-223 and pcDNA 3.1-STIM1 were transiently transfected into cancer cells independently or together, and then RT-qPCR was performed to detect the expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 40 publications
1
28
0
Order By: Relevance
“…24 The miR-223 levels were lower in breast cancer tissues and cells than those in normal tissues and cells, due to the fact that enforced miR-223 expression exhibited multiple anti-oncogenic effects in BC cells through silencing STIM1 expression. 25 In contrast, several studies had found high miR-223 expression in some cancers. In gastric cancer, upregulation of miR-223 more frequently occurred in tissues, cisplatin-resistant cells, and metastatic cells of gastric cancer, and high miR-223 expression markedly increased cancer cell metastasis, as well as stimulated cisplatin-induced apoptosis of resistant cells.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…24 The miR-223 levels were lower in breast cancer tissues and cells than those in normal tissues and cells, due to the fact that enforced miR-223 expression exhibited multiple anti-oncogenic effects in BC cells through silencing STIM1 expression. 25 In contrast, several studies had found high miR-223 expression in some cancers. In gastric cancer, upregulation of miR-223 more frequently occurred in tissues, cisplatin-resistant cells, and metastatic cells of gastric cancer, and high miR-223 expression markedly increased cancer cell metastasis, as well as stimulated cisplatin-induced apoptosis of resistant cells.…”
Section: Discussionmentioning
confidence: 94%
“…Compared with normal controls and chronic liver disease patients, patients with hepatocellular carcinoma exhibited significantly lower miR‐223 expression, indicating this miRNA had potential as an oncogene in hepatocellular carcinoma . The miR‐223 levels were lower in breast cancer tissues and cells than those in normal tissues and cells, due to the fact that enforced miR‐223 expression exhibited multiple anti‐oncogenic effects in BC cells through silencing STIM1 expression …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…M. Gao et al, 2018;He et al, 2018;Hummel et al, 2011;Lang & Zhao, 2018;Liao et al, 2018;Nicolè, Cappellesso, Sanavia, Guzzardo & Fassina, 2018;Q. Shi et al, 2017;Tan et al, 2017;Wang et al, 2018; L. Xu, Liu, Zhou, Chen, & Zhao, 2016;Yang et al, 2018;Zheng, Liu, Qiao, Zhang, & Lu, 2017;Zhu et al, 2016). These results are shown in Table 7.…”
Section: Deregulation Of Mirnas In Osteoporosismentioning
confidence: 89%
“…Note that not all targets have been assessed in vivo or using pharmacological agents. TRPA1(Takahashi et al 2018), TRPC1 (El Hiani et al 2009; Faouzi et al 2016; Schaar et al 2016), TRPC3 (Zhang et al 2012), TRPC5 (Ma et al 2012, 2014; Zhu et al 2015), TRPC6 (Aydar et al 2009), TRPM2 (Hopkins et al 2015; Koh et al 2015; Gershkovitz et al 2018a,b,c), TRPM7 (Guilbert et al 2009; Kim 2012; Davis et al 2014a), TRPV1 (Weber et al 2016), TRPV4 (Fiorio Pla et al 2012; Lee et al 2016; Peters et al 2017), TRPV6 (Bolanz et al 2008; Peters et al 2012), ORAI1(Yang et al 2009;Feng et al 2010;Badaoui et al 2018;Liu et al 2018b), ORAI3(Faouzi et al 2013;Motiani et al 2013;Hasna et al 2018), STIM1(Yang et al 2009(Yang et al , 2018, MCU(Curry et al 2013;Tosatto et al 2016), IP 3 R3(Szatkowski et al 2010;Mound et al 2017), Ca V 3.1 (Ohkubo and Yamazaki 2012), PMCA2 (VanHouten et al 2010; Curry et al 2016; Peters et al 2016), PMCA4 (Curry et al 2012), PIEZO1 (Li et al 2015), and PIEZO2 (Pardo-Pastor et al 2018). S.J.…”
mentioning
confidence: 99%